STUDENTS’ METACOGNITIVE AND CRITICAL THINKING SKILLS IN THERMOCHEMISTRY - Sudirman Sudirman; Yusnaeni Yusnaeni (Jurnal Tadris Kimiya, 2020)
Metacognitive is the ability to control cognitive aspects, while critical thinking is the ability to think rationally and clearly in understanding the logical connections between various ideas. Both are necessary in 21st -century education. This study aims to analyze students' metacognitive and their critical thinking skills in thermochemistry material and the correlation of metacognitive with critical thinking. The population was the third-grade private high school students consisted of four schools. Each school was randomly selected by one class as a sample, with a total sample of 150 students. Metacognitive skills instrument is an integrated essay test of metacognitive skills and critical thinking. The results showed that most of the students' metacognitive skills in the developing category (51.67%), most of the students' critical thinking skills in the sufficient category (65.33%), the students' metacognitive and critical thinking skill are positively correlated. The contribution of metacognitive abilities to critical thinking is at 72.0%. The results indicate that students' metacognitive and critical thinking skills need to be empowered to improving the quality of learning.